Analysis of Spelling and Syntactic Errors in Online News Texts: A Study in Modern Linguistics - Yolanda, Yolanda; Meywanthi, Nindha Iqlima; Saputra, Indra; Sitompul, Tresia Agustina; Mukhbita, Alya; Pebriana, Putri Hana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Syntactic studies in modern linguistics have undergone significant development, particularly in their application to mass media as a means of public communication. However, various spelling errors are still found in news writing, reflecting a lack of adherence to the rules of the Indonesian language as outlined in the General Guidelines for Indonesian Spelling (PUEBI). This article aims to analyze spelling errors in mass media news and examine their implications for Indonesian syntax. Using a descriptive qualitative approach, this study identifies common types of spelling errors, such as the use of capital letters, writing of loanwords, and punctuation. The results of the analysis show that spelling errors in mass media can affect syntactic structure and readers' understanding of the information conveyed. Therefore, it is essential for writers and editors in the media to understand and apply correct spelling rules in order to maintain language quality in public communication.